Discourse Network Analysis of Chemical Castration Punishment Pros and Cons in Online Media - Riki Handayani (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2024)
Sexual harassment continues to occur with an increasing number of victims. Chemical castration has been proposed as a solution, but it has sparked debates among experts and the public. This study examined the arguments for and against chemical castration in online media. It used the Discourse Coalition Framework and the Discourse Network Analysis approach to map this debate. The analysis included 84 statements from 32 news articles published on Detik.com between January 2016 and December 2022. The study revealed changes in the online discussions of chemical castration. The discourse shifted from the focus on norms and the purpose of punishment to the nature of punishment and its purpose. Subsequently, a discourse coalition emerged between the actors regarding chemical castration. The actors sought support from one another to support their respective positions. The discourse also changed along with groups of diverse views. Some rejected the law, arguing that it contradicts religious principles and does not guarantee a deterrence effect. Meanwhile, those who supported chemical castration continued to strengthen their arguments. In general, this study can be a reference for addressing sexual harassment.